Chlorinated Organics in Tropical Hardwood Kraft Pu1p and Paper Mill Effluents and their Elimination in an Activated Sludge Treatment System - Mohamed, Murtedza; Matayun, M; Lim, T.S (1989)
The identity and concentration of major chlorinated organics in the combined effluents of the SFI Pulp and Paper Mill in Sabah, Malaysia, were determined. In the biologically treated effluent, chlorinated organics found to occur in a relatively higher concentration were trichloroacetic acid (838-994 µg/L), 1,1-dichlorodimethyl sulfone (DDS) (86-232 µg/L), dichloroacetic acid (14-18 µg/L), and trichloro syringol (5-18 µg/L). Compared to those of a number of softwood kraft mills, the load of chlorinated phenols and acids in the wastewater of SFI hardwood kraft mill was 3-8 times lower. The effectiveness of oxygen activated sludge treatment system in eliminating these chlorinated organics was found to be as follows: chlorinated phenols 20-70 %, DDS 60 %, and chlorinated acetic acids 30-99%